Neuromuscular factors related to success in Olympic wrestling - Alfonso Martínez-Moreno; Vicente Morales Baños; Francisco Borrego (Federación Extremeña de Balonmano; University of Extremadura, 2011)
Abstract This study was undertaken to determine the relationship between maximum dynamic and isometric strength and success in male and female Olympic wrestling. Thirty-five female and thirty-seven male wrestlers were assigned into 4 groups according to their gender and competitive level: men elite (♂ ET, n = 18) and amateur (AT ♂, n = 19) and female elite (♀ ET n = 13) and amateur (AT ♀, n = 22). All subjects underwent assessments of body composition, countermovement jump, maximum dynamic strength test in full squat and bench press exercises and maximum isometric strength test of grip and hip extension. All the neuromuscular markers studied showed significantly higher values in the two elite groups compared to their respective amateur groups results, except the jump height between ♀ET y ♀AT, where no significant differences were detected. The present results suggest that the higher maximum isometric and dynamic strength values, explained in part by the differences in lean mass, will give elite wrestlers a clear advantage during the most frequently used techniques in Olympic wrestling.  Key  Words: bench press; squat; maximum dynamic strength; maximum isometric strength; combat.